OPTIMALISASI LAYANAN DRIVE THRU DI DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI JAWA TIMUR - Bahari, Ivan Cahya Putra; Hidayat, Endik (Jurnal Progress Administrasi Publik, 2024)
Optimizing the library drive-thru service is to improve the quality of a service owned by the East Java Provincial Library and Archives Office. This drive-thru service is in the form of a counter to serve the needs of library users without having to get out of the vehicle. Optimization of this public service aims to improve or increase the shortcomings of this drive-thru service so that it facilitates the services provided to users. The purpose of this research is to find out whether the services provided by the public services provided by the East Java Provincial Library and Archives Office are optimal or not. The focus of this research is Public Service Quality according to Zeithaml, Parasuraman, and Berry (in Hardiansyah 2011: 11) includes 5 variables consist of Physical Evidence, Reliability, Assurance, Responsiveness, and Attention. This type of research is descriptive with a qualitative approach. For data collection techniques used are interviews, observation, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, exposure, and conclusion drawing. The research informants were library librarians. The results showed that the optimization of drive-thru services has advantages and disadvantages. The physical evidence criteria, it shows that it is still not optimal because there are still some facilities that are not suitable for functioning. The reliability criterion shows that it is good because the officer in charge of the drive-thru service has been given a briefing regarding the technicalities. For the guarantee criteria, it is good because it guarantees fast service and free rates for drive-thru services. For the responsiveness criteria, it is good because the officers are quite responsive in serving the visitors, then the last criterion of attention is still not good because there is still a lack of awareness of officers to smile when serving the visitors. The suggestion that can be given is to encourage more socialization so that this drive-thru can be known by more people.   Keywords: Optimizing; Drive Thru; Library;  Librarian